Effect of Antioxidants On the achievement level Of National Weightlifting League - Ali, Hussein; Khalid, Omar (Journal of Physical Education, 2018)
Effect of Antioxidants On the achievement level Of National Weightlifting League The aim of the research is to design a program for Antioxidant Ultimate Nutrition supply of which contains vitamin C, E, A, Z, Glutathione (GSH), Selenium as well as identifying the effect of antioxidants on the level of advance weightlifters’ achievement. The researcher used the experimental method. The subjects were advance national league weightlifters. The experiment lasted for two months. The data was collected and treated using (SPSS). The results showed that antioxidants supply had a significant effect on the achievement level in pre and posttests in snatch and clean and jerk. The researcher recommended using antioxidants supply for athletes in various activities before and after training to upgrade the level of athlete. The researcher also recommended increasing the time period of the experiment to obtain better development in the research variables, especially with high level athletes.